The mediating effect of negative emotions on the relationship between subjective sleep quality and paranoia-like thoughts. (January 2022) - Bagrowska, Paulina; Pionke-Ubych, Renata; Majchrowicz, Kinga; Gawęda, Łukasz
Abstract: Sleep quality has been found to play an important role in paranoia-like thoughts both in clinical and non-clinical populations. Previous studies have shown that the presence of negative emotional states can mediate the link between sleep and paranoia, however, their role in the linkage is still not entirely clear. Hence, our study aimed to investigate further the mediating effect of negative emotions on the relationship between sleep quality and paranoia-like thoughts on a relatively large Polish sample drawn from the general population. We collected questionnaire data assessing paranoia-like thoughts, sleep quality and quantity, and negative affect from 604 Polish adults. We performed the correlation analysis and examined the mediating role of negative emotions in the relationship between sleep quality and paranoia. The results revealed significant moderate relationships between sleep quality and paranoia-like thoughts, negative emotions and paranoia-like thoughts, as well as between negative emotions and sleep quality. A mediation model for the relationship between sleep quality and paranoia-like thoughts revealed a complementary mediation by negative affect. The findings contribute to understanding the interrelatedness between sleep quality, negative emotions, and paranoia-like thoughts, as well as emphasize the importance of negative affect in the relationship between sleep and paranoia. Future research is needed to determine other factors that contribute to understanding the linkage as well as to determine the cause and effect.